Skipper's medical emergency handbook first air at sea - Briggs, Spike (Adlard Coles Nautical, 2008)
Designed to assist all who go to sea - whether on a day excursion, a holiday cruise or an even longer trip. It will provide practical advice, boost confidence, solve problems and minimise danger for all on board.